(untitled) (Bangladesh Journal of Zoology, 2020)
This study represents the comprehensive molecular identification of freshwater fishes of Bangladesh based on a fragment of the cytochrome c oxidase subunit I (COI) gene in the mitochondrial genome. A total of 315 mitochondrial COI barcode sequences were obtained from 153 species,114 genera, 49 families and 16 orders of fishes. The mean length of the sequences was 652 base pairs. For all the samples, %G was significantly lower compared to the other nucleotides and %GC was lower compared to %AT (p-value ˂ 0.05). Also, a significantly lower %GC content was observed in second and third codon position compared to the first one in all the samples (1st>2nd>3rd, p-value˂ 0.05). The average K2P distances within species, genera, families and orders were 0.38%, 7.02%, 12.75% and 18.68%, respectively. The mean interspecific distance was 18-fold higher than the mean intraspecific distance. The K2P neighbor-joining (NJ) trees based on the sequences generally clustered species according to their taxonomic position. A total of 12 species were newly recorded in Bangladesh. High efficiency in species identification were demonstrated in the present study by DNA barcoding, and concluded that COI sequencing can be used as an authentic identification marker for freshwater fish species. Bangladesh J. Zool. 48(1): 1-19, 2020